2022
DOI: 10.3390/jof8070684
|View full text |Cite
|
Sign up to set email alerts
|

Species Identification and In Vitro Antifungal Susceptibility of Paecilomyces/Purpureocillium Species Isolated from Clinical Respiratory Samples: A Multicenter Study

Abstract: Paecilomyces spp. are emerging fungal pathogens, where Paecilomyces lilacinus and Paecilomyces variotii are the most reported species. Taxonomic and phylogenetic revisions in this genus have shown that P. variotii represents a species complex, whereas P. lilacinus is related to another genus called Purpureocillium. The aims of this study were to identify clinical isolates of Paecilomyces spp. at the species level, and to determine their antifungal susceptibility profiles. 70 clinical Paecilomyces spp. isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The management of P. lilacinum infection is fraught with challenges manifested predominantly in its intrinsic resistance to amphotericin B. 5 Monpierre et al 6 extracted P. lilacinum from cultures of respiratory specimens of patients and tested their sensitivity to common antifungal agents in vitro. The final results showed that all azoles were active on P. lilacinum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of P. lilacinum infection is fraught with challenges manifested predominantly in its intrinsic resistance to amphotericin B. 5 Monpierre et al 6 extracted P. lilacinum from cultures of respiratory specimens of patients and tested their sensitivity to common antifungal agents in vitro. The final results showed that all azoles were active on P. lilacinum.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Voriconazole and posaconazole are novel azoles that have been effective against this fungal species. 6 Of note, voriconazole-resistant strains have already been found. 9,10 Thus, fungal identification and susceptibility testing are essential.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix-assisted laser desorption ionization-time of flight mass spectrometry is a tool that has shown its value for the identification of filamentous fungi where the concordance with molecular identification by sequencing reaches more than 98%. 136 The importance of species identification is major due to the differences in sensitivity to antifungal agents between species. 137 In addition, in the case of Aspergillus isolation, the determination of MICs for azole antifungals is relevant due to the increase in strains carrying azole resistance mutations.…”
Section: Non-culture-based Biomarkersmentioning
confidence: 99%
“…Paecilomyces variotii is resistant in vitro to voriconazole and isavuconazole, while remaining susceptible to amphotericin B, echinocandins, posaconazole, and itraconazole [ 88 , 191 , 192 , 193 ]. Case reports of breakthrough P. variotii disease in patients receiving voriconazole treatment or prophylaxis support the limited role for this agent [ 107 ].…”
Section: Management Of Sino-pulmonary Hyalohyphomycosesmentioning
confidence: 99%
“…P. lilacinum is generally susceptible to the triazoles with the lowest observed MICs for voriconazole and posaconazole. Activity of the echinocandins is variable [ 89 , 193 ]. Clinical studies also suggest good outcomes when voriconazole is used for invasive P. lilacinum disease, and one study demonstrated improved survival in patients treated with voriconazole rather than amphotericin B [ 89 , 194 ].…”
Section: Management Of Sino-pulmonary Hyalohyphomycosesmentioning
confidence: 99%